Deficiency of Dietary Fiber Modulates Gut Microbiota Composition, Neutrophil Recruitment and Worsens Experimental Colitis - Shen, Sj; Prame Kumar, Kathryn; Wen, Shu Wen; Shim, Raymond; Wanrooy, Brooke J.; Stanley, Dragana; Moore, Robert J.; Van, Thi Thu Hao; Robert, Remy; Hickey, Michael J.; Wong, Connie H. Y. (Frontiers in Immunology, 2021)
Ulcerative colitis is an inflammatory disease of the colon that is associated with colonic neutrophil accumulation. Recent evidence indicates that diet alters the composition of the gut microbiota and influences host-pathogen interactions. Specifically, bacterial fermentation of dietary fiber produces metabolites called short-chain fatty acids (SCFAs), which have been shown to protect against various inflammatory diseases. However, the effect of fiber deficiency on the key initial steps of inflammation, such as leukocyte-endothelial cell interactions, is unknown. Moreover, the impact of fiber deficiency on neutrophil recruitment under basal conditions and during inflammation in vivo is unknown. Herein, we hypothesized that a fiber-deficient diet promotes an inflammatory state in the colon at baseline and predisposes the host to more severe colitis pathology. Mice fed a no-fiber diet for 14 days showed significant changes in the gut microbiota and exhibited increased neutrophil-endothelial interactions in the colonic microvasculature. Although mice fed a no-fiber diet alone did not have observable colitis-associated symptoms, these animals were highly susceptible to low dose (0.5%) dextran sodium sulphate (DSS)-induced model of colitis. Supplementation of the most abundant SCFA, acetate, prevented no-fiber diet-mediated enrichment of colonic neutrophils and colitis pathology. Therefore, dietary fiber, possibly through the actions of acetate, plays an important role in regulating neutrophil recruitment and host protection against inflammatory colonic damage in an experimental model of colitis.